2013
DOI: 10.1007/s11033-013-2866-y
|View full text |Cite
|
Sign up to set email alerts
|

The drug-transporter gene MDR1 C3435T and G2677T/A polymorphisms and the risk of multidrug-resistant epilepsy in Turkish children

Abstract: One-third of all individuals with epilepsy are resistant to antiepileptic drug (AED) treatment. Antiepileptic treatment response has been suggested to be modulated by genetic polymorphisms of drug efflux transporters. Several polymorphic variants within the multidrug resistance 1 (MDR1) gene, which encodes the major transmembrane efflux transporter P-glycoprotein, have been proposed to be associated with AED resistance in epilepsy patients. The aim of this study was to evaluate the effect of C3435T and G2677T/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…The conflicting reports of several studies on genotype and allele frequency may be due to ethnic differences, knowing that gene polymorphisms often vary among ethnic groups, thus affecting the result of genetic studies. [28] Our findings are in partial agreement with these results, as we found the same differences between 1236CC and 1236TT genotypes distribution in our study groups. Thus, 1236CC was more frequent in resistant group compared with responsive patients (48.4 vs 19.3), while TT has been identified more frequent in responsive group (24.1 vs 22.6).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The conflicting reports of several studies on genotype and allele frequency may be due to ethnic differences, knowing that gene polymorphisms often vary among ethnic groups, thus affecting the result of genetic studies. [28] Our findings are in partial agreement with these results, as we found the same differences between 1236CC and 1236TT genotypes distribution in our study groups. Thus, 1236CC was more frequent in resistant group compared with responsive patients (48.4 vs 19.3), while TT has been identified more frequent in responsive group (24.1 vs 22.6).…”
Section: Discussionsupporting
confidence: 92%
“…and Haerian et al found no association between these SNPs and drug-resistant epilepsy. [28,29] In our study we found an association of the TT genotype variant of C1236T and also G2677T with responsive epileptic patients. Contradictions regarding the presence or absence of association between these polymorphisms and resistant epilepsies can be explained by differences related to the inclusion criteria.…”
Section: Discussionsupporting
confidence: 50%
“…C3435T and G2677T/A are the most common polymorphisms within the ABCB1 gene and are likely associated with variations in ABCB1 mRNA activity and/or expression (Moriya et al, 2002;Löscher et al, 2011). However, a series of case-control studies about C3435T polymorphism and resistance to AEDs yielded inconsistent results (Seo et al, 2006;Kim et al, 2006;Shahwan et al, 2007;Hung et al, 2007;Kim et al, 2009;Kwan et al, 2009;Vahab et al, 2009;von Stülpnagel et al, 2009;Grover et al, 2010;Dong et al, 2011;Kumari et al, 2011;Meng et al, 2011;Sayyah et al, 2011;Seven et al, 2014). Further, six meta-analyses (Bournissen et al, 2009;Haerian et al, 2010Haerian et al, , 2011aLeschziner et al, 2007;Nurmohamed et al, 2010;Li et al, 2014) attempted to analyze the findings of these case-control studies, but consistent results were not obtained due to the presence of between-study heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Cousar et al (2013) reported that the C allele of ABCB1 C3435T was associated with a better outcome of TBI patients compared with those carrying the T allele. However, Seven et al (2014) reported that the MDR1 C3435T and G2677T/A polymorphisms were not associated with antiepileptic drug resistance in Turkish epileptic patients. These inconsistent results may have been because different ethnicities were used, differences in sample size, or by chance.…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have investigated the association between ABCB1 polymorphisms and neurological disease (Liang et al, 2013;Cousar et al, 2013;Emich-Widera et al, 2013;Seven et al, 2014). Cousar et al (2013) reported that the C allele of ABCB1 C3435T was associated with a better outcome of TBI patients compared with those carrying the T allele.…”
Section: Discussionmentioning
confidence: 99%